2021
DOI: 10.1037/pst0000298
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of psychotherapists’ in-session tears.

Abstract: There is little empirical research on the topic of psychotherapists crying with or in front of clients (Blume-Marcovici, 2017); however, therapists crying in therapy appears to happen more frequently than previously believed (t' Lam, Vingerhoets, & Bylsma, 2018). Although many clients believe that crying in session improves their relationship with their therapist (Zingaretti, Genova, Gazzillo, & Lingiardi, 2017), it is unclear how therapists' tears impact the psychotherapy process. For example, as some researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Finally, occasionally the therapists reported that their crying was meant as a model for the patient how to handle grief or as an aid to accelerate the therapeutic process of a patient (’t Lam et al, 2018). Positive effects of therapist tears were found by Morgan and Nutt Williams (2020), who showed that, overall, the therapists had a consistent positive perception of the consequences of their own tears, both on therapy in general as well as on the patient–therapist relationship.…”
Section: Tears In the Clinical Settingmentioning
confidence: 97%
See 3 more Smart Citations
“…Finally, occasionally the therapists reported that their crying was meant as a model for the patient how to handle grief or as an aid to accelerate the therapeutic process of a patient (’t Lam et al, 2018). Positive effects of therapist tears were found by Morgan and Nutt Williams (2020), who showed that, overall, the therapists had a consistent positive perception of the consequences of their own tears, both on therapy in general as well as on the patient–therapist relationship.…”
Section: Tears In the Clinical Settingmentioning
confidence: 97%
“…Whether therapist tears are appropriate and helpful in the clinical context likely depends on several factors, including the therapist–patient rapport, the psychotherapeutic orientation, and whether the therapist tears would augment or distract from the therapy. Indeed, as advised by Morgan and Nutt Williams (2020, p. 1), In making decisions about when to cry or to suppress their tears, psychotherapists will need to assess on a case-by-case basis whether their tears, as a form of self-disclosure, are in the best service of the patient and will enhance the therapeutic process or detract from it.…”
Section: Recommendations For Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…doctor-patient; nurse-patient; therapist-client) (Blume-Marcovici, Stolberg & Khademi 2013;2015;Lutz 1999). Indeed, while recent studies have found between 72% (Blume- Marcovici et al 2013) and 87% (t ' Lam, Vingerhoets, & Bylsma 2018) of therapists report having cried in therapy, there are less than a handful of studies on this topic (Knox, Hill, Knowlton, Chui, Pruitt & Tate 2017;Morgan & Nutt Williams 2020). Findings from this small body of work have primarily focused on the therapeutic context of tears (e.g.…”
Section: Tears In the Counselling Roommentioning
confidence: 99%